Estudo teórico da interação de flúor em nanoestruturas de BC2N - Barbosa, Rafael de Carvalho (2011)
In this work we perform a theoretical study about fluorine adsorption in BC2N nanostructures. The fluorine interaction with the BC2N nanostructures was studied using only atomic fluorine on two nanotubos with different chiralities (zigzag(5,0) and armchair(3,3)) and a monolayer. We used first principles calculations based on the density functional theory (DFT) taking account the effects of the spin polarization. For the exchange and correlation term, we use the generalized gradient approximation (GGA) and to describe the electron-ion interaction we use the pseudopotential approximation. The charge density is obtained solving the selfconsistent Kohn-Sham equations and to represent the Kohn-Sham wave functions a linear combination of atomic orbital is used. Our results show that when a single fluorine atom is adsorbed, the most stable configuration occurs when the fluorine atom is adsorbed on the boron atom (FB). The configurations with the fluorine adsorbed on carbon atom (FCI and FCII) are less stable than the FB configuration and the FN reaction is unstable. When the fluorine atom is adsorbed in BC2N nanostructure the local configuration is modified. It is observed that the atom bonded to the fluorine atom moves outward from the surface of the nanotubes and the monolayer. The electronic properties present similar characteristics in both nanotubes and also in the monolayer. The FCII configuration introduce acceptors properties in a BC2N nanostructures and the FCI configuration introduce donor properties. The fluorine adsorption in the most stable configuration gives rise to electronic levels in the band gap. When we investigated the BC2N monolayer with different fluorine coverage, the most stable configuration is obtained when the fluorine atoms are adsorbed on the boron atoms, forming a line. Defects levels are observed near to the top of the valence band and the system exhibit a p-type semiconductor character to low fluorine density and metallic character to the high fluorine density. We observe that the fluorine adsorption induces spin polarization effects in BC2N nanostructures leaving the system to present a spin magnetic moment. The absolute value of the spin magnetic moment depends on the density of fluorine adsorbed.